Towards Billion-Body Dynamics Simulation of Granular Material - Shotwell, Rebecca; Negrut, Dan (Proceedings of the Wisconsin Space Conference, 2012)
Advances are being made in the simulation of granular material, such that billion- body simulations are, perhaps, feasible using a combination of existing hardware and new modeling software technology. This capability is predicted to lead to a better understanding of granular materials, contributing to many areas of research. However, these capabilities are only useful if they are shown to agree well with reality. Beginning at a simple level, a study was conducted to compare the simulation of primitive joints in the Chrono::Engine simulation package with the MSC/ADAMS commercial software package. This simple effort provides a measure for the accuracy with which the software models the interaction of a joint and one or two bodies. This allows more complex analyses to be carried out with knowledge of the softwareâ€™s accuracy at this level.Â 